Induction of intrinsic and extrinsic apoptosis pathways in the human leukemic MOLT-4 cell line by terpinen-4-ol - Khaw-on,P. (Asian Pacific Organization for Cancer Prevention, 2015)
Terpinen-4-ol is a terpene found in the rhizome of Plai (Zingiber montanum (Koenig) Link ex Dietr.). In this study apoptogenic activity and mechanisms of cell death induced by terpinen-4-ol were investigated in the human leukemic MOLT-4 cell line. Terpinen-4-ol exhibited cytotoxicity in MOLT-4 cells, with characteristic morphological features of apoptosis by Wright's staining. The mode of cell death was confirmed to be apoptosis by flow cytometric analysis after staining with annexin V-FITC and propidium iodide. A sub-G1 peak in DNA histograms of cell cycle assays was observed. Terpinen-4-ol induced-MOLT-4 cell apoptosis mediated through an intrinsic pathway involving the loss of mitochondrial transmembrane potential (MTP) and release of cytochrome c into the cytosol. In addition, terpinen-4-ol also induced apoptosis via an extrinsic pathway by caspase-8 activation resulting in the cleavage of cytosolic Bid. Truncated-Bid (tBid) translocated to mitochondria and activated the mitochondrial pathway in conjunction with down-regulation of Bcl-2 protein expression. Caspase-3 activity also increased. In conclusion, terpinen-4-ol can induce human leukemic MOLT-4 cell apoptosis via both intrinsic and extrinsic pathways.